PENGARUH MASYARAKAT MISKIN TERHADAP MOTIVASI BELAJAR ANAK DIKELURAHAN SIMPANG BARU KECAMATAN TAMPAN PEKANBARU - Novi Kurniawati; Hambali '; Gimin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this reseah toeducation foor people was necessary for the moment, because, with the levelof the higher necessities of life, caused the group is increasingly difficult to follow the education process. In fact the educational process. In fact for the educational proces “as is“ do they have trouble, what else to follow the process of education and learning quality is school is no longer affordable for the family financial situation. While to follow the education process in school that “what is” not yet able to provide enlightenment to the fullest. Therefore the formulation of the problem of this research is “How The Influence of the Poor against the child Motivation to learn In The Village Of Simpang Baru Subdistrict Tampan Pekanbaru?”, with the aim to determine the effect of the poor to children learning Motvation in The Village Of Simpang Baru Subdistrict Tampan Pekanbaru. This research method is quantitative descriptive. Collection instrument used in this study is a questionnaire consisting of 14 question about the effect of the poor (variable X) and the children learning motivation (variable Y). were analyzed using linear regression and F test so the hypothesis that states “there is the influence between the poor to motivation children learning in The Village Of Simpang Baru Subdistrict Tampan Pekanbaru.” With a series of simple regresson test between the variable X and Y, obtained Fcount 2,712 and Ftable value 4,35 wich obtained from the study of the distribution list Ftable with N=22 poor society and N=22 children learning motivation, at significance level of 5% thus Fcount < Ftable, or 2,712<4,35. So the hyphotesis in this study denied that there is no significant influence among the poor on motivation against children study in The Village Of Simpang Baru Subdistrict Tampan Pekanbaru.Key Words: Influence, community poor, motivation learn child